Rapid, Scalable Assembly of Stereochemically Rich, Mono- and Bicyclic Acyl Sultams - Asad, Naeem (2013)
[Image: see text] A one-pot, sequential protocol is reported that involves complementary ambiphile pairing (CAP) of a vinyl sulfonamide with a variety of unprotected amino acids via aza-Michael addition and subsequent intramolecular amidation. The method generates diverse, sp(3)-rich mono- and bicyclic acyl sultams in a highly scalable manner. Modular pairing of stereochemically rich building blocks allows quick access to all possible isomers. Extension to include one-pot, sequential 3-, 4- and 5-multicomponent protocols is also discussed.